Pengaruh Kebijakan Office Channeling, Dana Pihak Ketiga (DPK) Dan Penyaluran Pembiayaan Terhadap Aset Perbankan Syariah Di Indonesia (Periode 2017-2021) - Hasibuan, Abdi Satria; Nurbaiti, Nurbaiti; Syarvina, Wahyu (Universitas Labuhanbatu, 2023)
This study aims to evaluate the impact of Third Party Funds (DPK), Office Channeling Policies, and Financing on Islamic Banking Assets in Indonesia from 2017 to 2021. The type of research applied in this research is quantitative. The data source used is primary data derived from a sample of Islamic banking companies in Indonesia from UUS. Data collection was used by applying purposive sampling by distributing to 10 names of Islamic banking companies who were respondents. This work utilizes the method of multiple linear regression analysis. The research findings show that: 1) Office Channeling policies have a significant impact on Islamic Banking Assets; 2) Third Party Funds (DPK) have a significant influence; 3) Financing has a significant impact; and 4) Office Channeling Policies, Third Party Funds (DPK), and Financing have a significant impact. According to the analysis of the findings of the multiple linear regression study, financing (1,000), third party funds (DPK) (1,025), and office channeling policies (0,980) all have a beneficial effect on Islamic banking assets (0,014).